2012
DOI: 10.1007/s13277-012-0485-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of autotaxin and lysophosphatidic acid receptor 3 with aggressiveness of human breast carcinoma

Abstract: In vitro and in vivo experimental studies have demonstrated the role of lysophosphatidic acid (LPA) signaling in tumor proliferation, invasiveness, and metastasis. Among LPA receptors, the overexpression of LPA receptor 3 (LPAR3) in transgenic mice has resulted in the highest rate of breast cancer metastasis. Our goal is to evaluate the LPA-producing enzyme autotaxin and LPAR3 as potential therapeutic targets in breast cancer patients. The expression of autotaxin and LPAR3 was examined by immunohistochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 29 publications
6
37
1
Order By: Relevance
“…Qualitatively, TAg mouse mammary fat pads stained much more intensely for ATX and the adipocytes tended to be smaller. These data agree with previous studies suggesting that mammary tumorigenesis increases ATX expression in the mammary stroma (32,38). …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Qualitatively, TAg mouse mammary fat pads stained much more intensely for ATX and the adipocytes tended to be smaller. These data agree with previous studies suggesting that mammary tumorigenesis increases ATX expression in the mammary stroma (32,38). …”
Section: Resultssupporting
confidence: 93%
“…For example, we observed a striking increase in ATX expression in the stromal-compartment of TAg vs. parental mouse mammary glands. Similar observations were made in two other studies, one in human breast cancer and the other in a mouse model (32, 38). In a panel of 87 invasive human breast carcinomas, Popnikolov et al reported increased stromal ATX expression in 16.3% of samples, and high ATX expression was associated with strong desmoplastic stromal reactions (32).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a colon cancer cell line, LPA increases the synthesis of macrophage migration inhibitory factor, which also promotes tumor growth ( 133 ). Women with breast carcinomas that express high levels of LPA 3 receptors in epithelial cells, or ATX in stromal cells, have larger tumors, nodal involvement, and higher stage disease ( 134 ).…”
Section: Lpp3 and The Vasculaturementioning
confidence: 99%
“…There are also a host of soluble molecules in the tumor and this heterogeneity adds another layer of complexity to ATX/LPA signaling. Popnikolov et al showed that immunohistochemical staining for ATX in stromal cells and LPA 3 and cancer epithelial cells correlate positively with cancer aggressiveness [75] . This study highlights the role of ATX from tumor stroma as a producer of LPA for cancer progression.…”
Section: Overview Of the Atx-lpa-lpp Axis Atx -The Predominant Producmentioning
confidence: 99%